The Employability of Government Institution: The Role of Job Crafting and Creative Climate Moderator - Ersaliya Arezah; Fathul Himam (Gadjah Mada Journal of Psychology (GamaJoP), 2023)
The evolution of technology led to rapid changes that affected both organizations and employees. Employability was a term to describe a continuum process of fulfilling the skills and expertise that also changed rapidly. One’s behavior in crafting a job could lead to one’s employability. Organizational climate, which in this study was the creative climate, had a moderating role in affecting the job creation toward employability. This study aimed to explain the role of job crafting in predicting employability in government institution X and creative climate as the moderator. The quantitative approach was applied to this research, by distributing Employability Scale (α = 0.937), Job Crafting Scale (α=0.922), and Creative Climate Scale (α=0.950) to 129 employees of government institution X. The study showed that job crafting significantly predicted the employability (R2 = 56.7%; p = 0.000, p < 0.05) along with creative climate lessened the prediction of job crafting to employability (p = 0.027, p < 0.05). Thus, the hypothesis in this study was accepted. Therefore, it was worth noting that job crafting had benefits for employees’ employability with a constructive, suitable organizational climate.